Enterprise, Money and Credit in England before the Black Death 1285-1349 - Nightingale, Pamela (Palgrave Studies in the History of Finance,, 2018)
This book charts the contributions made to the development of the late medieval English economy by enterprise, money, and credit in a period which saw its major export trade in wool, which earned most of its money-supply, suffer from prolonged periods of warfare, high taxation, adverse weather, and mortality of sheep. Consequently, the economy suffered from severe shortages of coin, as well as from internal political conflicts, before the plague of 1348-9 halved the population. The book examines from the Statute Merchant certificates of debt, the extent to which credit, which normally reflects economic activity, was affected by these events, and the extent to which London, and the leading counties were affected differently by them. The analysis covers the entire kingdom, decade by decade, and thereby contributes to the controversy whether over-population or shortage of coin most inhibited its development. .